Indian Dermoscopic Study of One Thirty Eight Cases of Alopecia Areata - Rajendra Kumar Sharma, Rahul Kumar Sharma, Divya Sharma, (International Journal of Innovative Research in Medical Science, 2018)
Alopecia areata (AA) is a type of non-scarring alopecia first described by Cornelius Celsus, characterized by hair loss without any clinical inflammatory signs and affecting both males and females equally. The activity of AA is by the presence of black dots, broken hair, and tapering, furthermore black dots and yellow dots are equated to severity of AA. Aim - To study dermoscopic features of untreated cases of alopecia areata. Study subjects-All the patients who attended the dermatology clinic from March 2015 to March 2017 with the clinical diagnosis of alopecia areata and who fulfilled the inclusion and exclusion criteria. Study period - Two year (from March 2015 to March 2017). Methodology - All the patients who attended the dermatology clinic from March 2015 to March 2017 with the diagnosis of alopecia areata and who fulfilled the inclusion and exclusion criteria were recruited for the study. Trichoscopy was performed with DL4 dermatoscope. The images were further magnified with smart phone. Results - We got various dermoscopic signs in different combinations in our study. Yellow dots were seen in 10 cases, White dots in cotton wool pattern were seen in 3 cases, Black dots were seen in 25 cases, Dermoscopic coudability sign was demonstrated in 38 cases, Pigtail hairs were present in 2 cases, five cases showed short vellus hairs, Short broken hairs were found in 18 cases, Exclamation mark hairs were very common and were detected in 131 patients out of 138. Discussion - Single feature is not leading to the diagnosis so we should use combination of features which will help in difficult cases like AA incognito. Dermatoscope is an indispensible valuable tool in trichology practice which helps in prognosticating and making early diagnosis of AA. It also helps to differentiate it from trichotillomania and other causes of alopecia. In our study the incidence of AA was almost similar in both sexes. Our study revealed that exclamation mark hair is very common and sensitive dermoscopic marker of AA.